Prevalence of prolonged grief disorder and its symptoms among bereaved individuals in China: a systematic review and meta-analysis - Bao-Liang Zhong; Meng-Di Yuan; Jun-Fa Liu (General Psychiatry)
Background The prevalence of prolonged grief disorder (PGD) and its symptoms among the bereaved population in China vary considerably.Aims This meta-analysis aims to estimate the prevalence of PGD and its symptoms among bereaved individuals in China.Methods We conducted a literature search in major Chinese and English databases from their inception to 4 October 2023, for cross-sectional studies on the prevalence of PGD or its symptoms in bereaved Chinese individuals. The risk of bias of the included studies and certainty of the evidence were assessed using the Joanna Briggs Institute Critical Appraisal Checklist for Studies Reporting Prevalence Data (‘JBI checklist’) and the Grading of Recommendations, Assessment, Development and Evaluations (GRADE), respectively. The ‘metaprop’ package in R V.4.1.2 was used to synthesise the prevalence.Results A total of 28 studies involving 10 994 bereaved individuals were included in the analysis, with JBI checklist scores between 3 and 7. The combined prevalence (95% confidence interval) of PGD and its symptoms was 8.9% (4.2% to 17.6%) and 32.4% (18.2% to 50.8%), respectively. PGD and its symptoms were most prevalent among those who had lost their only child (22.7%) and those bereaved by earthquakes (80.4%), respectively. The GRADE system assigned a very low certainty level to the evidence for the pooled prevalence of PGD and its symptoms.Conclusions The pooled prevalence of PGD and its symptoms indicate a potential high need for grief counselling services among bereaved individuals in China. This need is particularly pronounced in those who have lost their only child and those bereaved due to earthquakes. Further methodologically rigorous studies are needed to provide more accurate prevalence estimates.PROSPERO registration number CRD42023432553.